Photoacoustic characterization of phase transitions in amorphous metal alloys - Orzi, Daniel Jesús Omar (1998)
In this work a pulsed laser photoacoustic technique is employed in amorphous alloys for the characterization of crystallization temperatures and the determination of the activation energies for the transitions. It is shown that the changes produced in the photoacoustic signal generated by low energy laser pulses (< 200 μJ), is a sensitive probe for detecting the crystallization of a metallic amorphous sample. A piezoelectric transducer attached to the sample by means of a glass substrate was used for the acoustic detection. The developed technique has the advantages of requiring a minimum amount of sample, with no special sample preparation or conditioning. In order to demonstrate the validity of the technique, it was applied to the study of the crystallization processes of the amorphous Mg-Zn alloy, comparing the result with respect to resistivity measurements.